Triphala Seed Stones-Derived Nanoporous Activated Carbon Materials with Excellent Adsorption Applications - Gnawali, Chhabi Lal; Rajbhandari, Rinita; Pokharel , Bhadra Prasad (Journal of the Institute of Engineering, 2023)
Biomass-derived activated carbon materials with nanoporous structure exhibit high surface area due to well-defined pore structure as a result of which the activated carbon from biomass could be suitable materials for high performance separation, purification technologies and energy storage application as efficient adsorbent. Here, the novel nano-porous activated carbon from Triphala (Harro, Barro and Amala) seed stones by chemical activation using Zinc Chloride as an activating agent is presented. The prepared activated carbon is characterized by iodine and methylene blue adsorption properties and scanning electron microscopy (SEM). Keeping other parameter constant, the effect of carbonization temperature of the activated carbon was studied. The experimental result indicates that Triphala seed stones and Zinc Chloride at mixing ratio1:1 by weight, carbonized for 4 hours at 500 0C shows high value of iodine number and methylene blue number as 856.8 mgg-1 and 373.5 mgg-1 respectively. The surface area, micropore volume and the total pore volume of the sample using quadratic model was found to be 908.9 m2g-1, 0.827 cm3g- and 0.932 cm3g-1 respectively. The prepared activated carbon possesses well-defined pore-size distribution with nanoporous structure These results show that Triphala seed stones derived nanoporous activated carbon will be a suitable material for water purification as well as energy applications.